Gender inclusiveness in the adoption and use of home energy technologies - Tuomela, Sanna; Iivari, Netta; Hänninen, Tuomo; Svento, Rauli (Association for Information Systems, 2023)
Home energy technologies, such as smart home energy management systems (SHEMS), are important in reducing energy-related emissions and empowering energy users. However, there are concerns on gender inclusiveness of the adoption and use of SHEMS. So far, information systems research has failed to address this significant challenge. This study examines factors shaping gendered adoption and use of smart home technologies, particularly SHEMS, and the implications this has for sustainability and energy equality. Applying a critical lens, we examine findings from a sensory ethnographic study on the adoption of SHEMS in households. The findings underline the need for more inclusive energy technology design, more understanding of diversity of households and more variety in the approaches for increasing awareness on and facilitating the adoption of energy technologies. We contribute to research on gender and home energy technologies, and to the larger discussion of gender and energy.
Keywords: Smart home energy management systems; gender inclusiveness; sensory ethnography; user experience